2018
DOI: 10.1007/s11748-018-0950-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary capillary hemangiomatosis diagnosed by pathology of explanted lungs: a unique etiology serves as a key of clinical diagnosis

Abstract: A 27-year-old female patient had presented progressing exertional dyspnea due to pulmonary hypertension. Chest CT revealed diffusely spread patchy ground-glass opacities sparing subpleural parenchymal areas suggesting the diagnosis of pulmonary veno-occlusive disease (PVOD). Despite the diagnosis of PVOD, she was somehow managed by a repetitive escalation of the epoprostenol dose and oxygen supply during the 12-month waiting period until successful bilateral lung transplantation was performed. Pathology demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Montani et al [10] have reported that occupational exposure to organic solvents might present a risk factor for PVOD. Although crucial causes of risk factors of PCH have not been identified yet, PCH can be developed secondarily in lungs with PVOD, connective tissue diseases, and chronic passive congestion based on a few case reports [19]. Considering the above relation between PCH and PVOD, occupational exposure to silica or organic solvent in the current patient might have influenced the clinical course of PCH, although whether and to what extent of the exposure might be related to the development of PCH are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Montani et al [10] have reported that occupational exposure to organic solvents might present a risk factor for PVOD. Although crucial causes of risk factors of PCH have not been identified yet, PCH can be developed secondarily in lungs with PVOD, connective tissue diseases, and chronic passive congestion based on a few case reports [19]. Considering the above relation between PCH and PVOD, occupational exposure to silica or organic solvent in the current patient might have influenced the clinical course of PCH, although whether and to what extent of the exposure might be related to the development of PCH are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Typical pattern of CT in PCH and PVOD. (a) Unique pattern of PCH: GGOs distributed diffusely in a bat-wing pattern in the lung field, sparing subpleural parenchyma, 10 (b) typical pattern of PCH: diffuse centrilobular GGOs with poorly defined nodular pattern, 13 and (c) typical pattern of PVOD: centrilobular GGOs with poorly defined nodular pattern, septal lines, and mediastinal lymph node enlargement (white dotted lines). 6 enlargement were observed less frequently (19% and 12%, respectively) than in PVOD.…”
Section: Discussionmentioning
confidence: 99%
“…Among these cases, only two cases reported the findings of BAL. 10,11 Conversely, no cases reported transbronchial lung biopsy (TBLB). However, ''lung biopsy'' (not including open lung biopsy) was performed in four cases ( Table 2).…”
Section: Physiological Findings (Pfts and Bal)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nomenclature and terminology continue to be problematic in the field of lung alveolarization and BPD. A recent plea was made for the proper pluralization of "septum" as "septa" (402), and yet, the continued use of the incorrect "septae" persists in the "lung literature," (56,226,234,347,350,422,424,551,607). The pluralization of "alveolus" has also seen the recent introduction of a new misnomer: "alveolae" (594) instead of the correct form, "alveoli.…”
Section: Nomenclaturementioning
confidence: 99%